THE INFLUENCE OF PRICE PERCEPTION AND PRODUCT QUALITY ON PURCHASING DECISIONS AT JAGO COFFEE WITH CONSUMER TRUST AS A MODERATING VARIABLE - Rizatullah Ramdani; La Diadhan Hukama (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2025)
The purpose of this study is to analyze the influence of price perception and product quality on purchasing decisions with consumer trust as a moderating variable in YARSI University students as consumers of Jago Coffee and its review from an Islamic perspective. This study involved a sample of 180 respondents with a purposive sampling technique. Data collection was carried out through a survey method with a questionnaire and analyzed using the Partial Least Square Structural Equation Modeling (PLS-SEM) method and processed using SPSS and Warp PLS applications. The results of the model evaluation indicate that price perception, product quality, and consumer trust have a high level of suitability and are relevant in predicting their influence on purchasing decisions. The results of this study reveal that price perception and product quality each have a positive and significant influence on purchasing decisions. Furthermore, consumer trust has not been able to moderate the influence of price perception and product quality on purchasing decisions.